Acute, major muscular hematoma associated with antithrombotic agents: A multicenter real-world cohort. Issue 199 (March 2021) - Bouget, Jacques; Huet, Marie-Clémence; Roy, Pierre-Marie; Viglino, Damien; Lacut, Karine; Pavageau, Laure; Oger, Emmanuel
Abstract: Background: There is little data on major muscular hematomas and the little there is has mainly focused on patients exposed to oral anticoagulants. Objective: To describe the clinical characteristics, management and outcomes of patients admitted to emergency department (ED) for major muscular hematoma associated with an antithrombotic agent, and to identify predictors of in-hospital mortality. Patients and methods: Over a three-year period, all consecutive cases of adult patients admitted to the ED of 5 tertiary care hospitals for major muscular hematoma while exposed to an antithrombotic agent were prospectively collected and medically validated. Clinical and biological data, therapeutic management of the bleeding event, and in-hospital mortality were collected from the medical records and compared across five groups of hematoma locations. Potential confounders were taken in account using a multivariate binomial regression model. Results: Three hundred and seventy-five patients were included (mean age = 81.4 years): 271 were exposed to vitamin K antagonists, 58 to parenteral anticoagulants (heparin, LMWH, fondaparinux), 33 to antiplatelets, and 13 to direct oral anticoagulants. The muscular hematomas were located in the lower limbs (n = 198), the rectus sheath (n = 71), the iliopsoas (n = 45), the upper limbs (n = 33), or elsewhere (n = 28). Reversal therapy was prescribed for 48.5% of patients, red cell transfusions for 63.6%, surgery for 12.3% and embolization for 3.5%. For 84% of patients, hospitalization was required, with a median length of stay of 10 days. Overall, in-hospital mortality was 8.5%. Reversal therapy, the need for intensive care and mortality were significantly more frequent among patients with iliopsoas hematomas. The independent predictors of in-hospital mortality were: decrease in mean arterial pressure (RR = 1.84), decrease in hemoglobin level (RR = 1.37) and the iliopsoas location (RR = 3.06). Conclusion: Frail elderly patients with major muscular hematomas linked to antithrombotic agents risk substantial morbidity and in-hospital mortality. The iliopsoas location was the most life-threatening bleeding site. Close observation of this population is warranted to ensure better outcomes. Highlights: Data on major muscular hematomas while exposed to any antithrombotic agents are lacking. Major muscular hematomas were mostly located in the lower limbs. Iliopsoas location was an independent predictor of in-hospital mortality.